2021
DOI: 10.3389/fcell.2021.725933
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental and Pathological Hypoxia on Male Fertility

Abstract: Male infertility is a widespread health problem affecting approximately 6%–8% of the male population, and hypoxia may be a causative factor. In mammals, two types of hypoxia are known, including environmental and pathological hypoxia. Studies looking at the effects of hypoxia on male infertility have linked both types of hypoxia to poor sperm quality and pregnancy outcomes. Hypoxia damages testicular seminiferous tubule directly, leading to the disorder of seminiferous epithelium and shedding of spermatogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 234 publications
(270 reference statements)
0
12
0
1
Order By: Relevance
“…And after strict quality screening, a total of 4849 articles with an average citation per year of 1 or more were selected for bibliometric analysis. Fertility have been a hot topic of concern, and approximately 6% – 8% of men are afflicted with fertility problem, while spermatogenesis is essential for male fertility (Kesari et al, 2018 ; Li et al, 2021 ; Pereira et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…And after strict quality screening, a total of 4849 articles with an average citation per year of 1 or more were selected for bibliometric analysis. Fertility have been a hot topic of concern, and approximately 6% – 8% of men are afflicted with fertility problem, while spermatogenesis is essential for male fertility (Kesari et al, 2018 ; Li et al, 2021 ; Pereira et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that merely a few amino acid metabolism pathways were enriched by DEGs in inter-breed female comparison in this study ( Figure 3 ). One previous study has shown that the maintenance of redox homeostasis can promote meiotic maturation of porcine oocytes ( Li Z, et al, 2021 ). These findings jointly suggested that amino acid metabolism imbalance induced by mitochondrial oxidative phosphorylation might be one of the early causes behind meiotic failure, which was consistent with our speculation on the reason for male Mule duck sterility.…”
Section: Discussionmentioning
confidence: 99%
“…This difference between the testis and epididymis may be because the immune response in the testis during sperm development is different from that seen in the epididymis when sperm is matured 6 . The results of several studies have shown that elevated levels of pro‐inflammatory cytokines are associated with spermatogenesis disorders, poor sperm quality, and infertility 44–46 . To sum up, the above data suggested that non‐infectious inflammation of mouse testis and epididymis induced by Hadh knockout affects spermatogenesis and sperm maturation in male mice, and inflammatory factors TNF‐α has a key role in the molecular mechanism of this Hadh −/− mice model.…”
Section: Discussionmentioning
confidence: 99%